Legal research and legal citation - Oseni, Umar Aimhanosi (Malaysian Current Law Journal, 2014)
Generally, one of the most important factors that establish the veracity of particular facts is the evidence adduced to support such facts. Just as a lawyer in a court of law is required to adduce evidence to support his or her statement of fact, a legal research is required to provide the relevant details, sources, and references to justify any statement or submission made during the course of a research. Therefore, legal research and legal citation are two important aspects of legal method that are closely related. This chapter provides an introduction to legal research and gives step-by-step guidelines on how to conduct research as greenhorns in the legal field. At the end of the chapter the student should be able to: (1) Explain what constitutes legal research in the study of law; (2) Understand the relationship between legal research and legal method; (3) Acquire the ability to identify the different types of legal research; (4) Understand the relevance and types of legal citations; and (5) Conduct a successful legal research.